Analysis of Factors Affecting Industrial Engineering Students' Learning Interest in the Online Lecture System - Sarbini Sarbini; M. Baidawi (Widyagama University of Malang, 2021)
The COVID-19 pandemic has forced universities, lecturers, and students to suddenly migrate from face-to-face learning to online learning. in early 2020 these three components must adapt to the situation, but after 2 semesters of adaptation had taken place, the factors that influenced students in attending online lectures are the factor of lecturers and students’ adaptability to the software used, the factor of phone signal in the area where the students live, and the factor of limited funds for data. These factors will affect the students’ comfort factor and shape their interest in the online learning system. This research used a sample of Industrial Engineering students to produce the factors that influence learning interest in the online system. From the descriptive data analysis, it reveals that students perceive lecturer adaptation to online learning as quite good, the quality of the network as tolerable, although there are areas where the internet signal is considered weak. The students’ experience of online lectures is a little less satisfactory. The highest scores of students' expectations for future teaching system are: 48% for a 50% online and 50% offline system, 75% for a pure offline system, and 25.6% for a 25% online system. The relationship between students' perceptions of the adaptability of lecturers, internet quality and their experiences of online lectures affect the student’s comfort in online lectures in the form of a linear regression.